Profile Matching untuk Menentukan Besaran Kenaikan Gaji Karyawan pada PT. Eka Mandiri Sukses - David David; Marfuah Marfuah (Journal of Applied Science and Technology, 2022)
Every company wants the best and maximum results in every production process. To achieve the best results in the production process/company activities, it is necessary to have support from every aspect of the company such as employees, supporting facilities, etc. One of the efforts to improve employee performance is support from the company in the form of salary increases. In the process of determining/considering an increase in employee salaries in the company, there are several obstacles or problems that will be encountered/faced by the company, including time efficiency, calculating employee performance, and the number of employee data files that must be processed. Decision Support System is a system to support material decision makers / makers in terms of semi-structural decisions. The profile matching method is a method for solving a problem so as to rank the best candidates from predetermined criteria. This study uses several criteria in decision making including work attitude, personality and responsibility, Based on 3 employee data, the final result is A01 and A02 getting a 5% increase in basic salary while A03 is 4%. and the results of this study is to use the Profile Matching method to find out the ranking or value weights in the assessment of the best employees, in the results of this study it helps in making decisions more quickly and accurately and the results can be accounted for. This research aims to be able to help PT. Eka Mandiri Success in determining employee salary increases// // //